Electrochemical, Adsorption and Anticorrosion Study on Fluvoxamine and its Blends for X80 Steel Protection in Well Acidizing Fluids - Ituen,Ekemini (2016)
Corrosion of steel pipes, tubing, and casings in the oilfield by acidizing fluids is a major cause of materials failure. Corrosion of X80 steel in hydrochloric acid, a typical acidizing solution, was probed using gravimetric and electrochemical techniques. Fluvoxamine (FLU) was used as anticorrosive additive to the acid, and monitored between 30 °C to 90 °C. FLU offered efficient protection for the X80 steel by inhibition. The inhibitive effect increased with a higher FLU concentration, but decreased as temperature increased. The highest concentration of FLU (10×10-5 M) afforded inhibition efficiency of 93.5% and 80.4% in 1 M and 15% HCl, respectively, at 30 oC. The efficiency decreased to 88.5% and 73.3%, respectively, at 90 °C. Inhibition efficiency was improved by blending FLU with glutathione, polyethyleneglycol and potassium iodide. Adsorption and thermodynamic studies reveal that the inhibitor functions, by spontaneous exothermic adsorption on X80 surface, were best described by Langmuir adsorption model. Impedance measurement reveals increase in charge transfer resistance with decrease in double layer capacitance. Polarization studies show that FLU acts as a mixed type inhibitor. Scanned micrographs of X80 surface show a lower pitting in the presence of FLU than in the free acid, demonstrating the effectiveness of FLU as X80 steel corrosion inhibitor.